Bilateral Undescended Testes in an Old Male Cadaver: A Rare Anatomical Discovery - Amirhossein Mohammadi; Hamidreza Asgari (Negah Institute for Scientific Communication, 2023)
Introduction: Cryptorchidism is a congenital condition characterized by undescended testes, typically observed in infancy. We present an unusual case of bilateral undescended testes during anatomical dissection. Case Report: The cadaver, preserved using standard techniques, exhibited bilateral undescended testes with no apparent signs of testicular issues or malignancies. The left testis was situated near the superficial ring of the inguinal canal, while the right testis was located deeper within. Both testes displayed normal size and structure, with intact vas deferens and blood vessels.  Clinical Implications: The etiology of adult-onset bilateral cryptorchidism remains unclear, emphasizing the importance of early diagnosis in living patients. Timely intervention is crucial, as undescended testes in adults can lead to infertility, increased cancer risk, and hormonal imbalances. This case underscores the significance of regular medical examinations and early management for cryptorchidism. Conclusion: This rare case highlights the necessity of considering cryptorchidism in adult patients, even in the absence of apparent symptoms or malignancies. The findings emphasize the importance of prompt diagnosis and intervention to mitigate potential complications. Further research into adult-onset cases is warranted to enhance clinical understanding and improve patient care.